Institutions, Holdup and Automation - Giorgio Presidente (ZBW - Leibniz Information Centre for Economics, 2021)
What drives investment in automation technologies? This paper documents a positive relationship between labor-friendly institutions and investment in industrial robots in a sample of developing and advanced economies. Institutions explain a substantial share of cross-country variation in automation. The relationship between institutions and robots is stronger in sunk cost-intensive industries, where producers are vulnerable to holdup. The result suggests that one reason for producers to invest in automation is to thwart rent appropriation by labor. As a consequence, policies aimed at supporting workers' welfare by increasing their bargaining power might actually reduce their employment opportunities.
Keywords: O32; O33; L16; J50; O57; 330; Robots; Institutions; automation; holdup; unions; sunk costs; appropriability; bargaining; frictions; rents; technology adoption